2017
DOI: 10.1158/0008-5472.can-16-2072
|View full text |Cite
|
Sign up to set email alerts
|

Poor Prognosis Indicated by Venous Circulating Tumor Cell Clusters in Early-Stage Lung Cancers

Abstract: Early detection of metastasis can be aided by circulating tumor cells (CTCs), which also show potential to predict early relapse. Due to the limited CTC numbers in peripheral blood in early stages, we investigated CTCs in pulmonary vein blood accessed during surgical resection of tumors. Pulmonary vein (PV) and peripheral vein (Pe) blood specimens from patients with lung cancer were drawn during the perioperative period and assessed for CTC burden using a microfluidic device. From 108 blood samples analyzed fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(141 citation statements)
references
References 56 publications
17
124
0
Order By: Relevance
“…For early stage lung cancer, due to the difficulty of tissue biopsy, there is still a lack of sensitive biomarkers to predict TMB and oncogenic driver mutations before surgery. With the development of liquid biopsy techniques, such as circulating tumor DNA (ctDNA) or circulating tumor cells (CTCs), it is possible to obtain the genomic mutation status from a blood sample; however both the sensitivity and cost are prohibitive Our study demonstrated that selected radiomics signatures using machine learning technique are feasible and effective to predict TMB and some driver mutations (EGFR and TP53) in patients with early stage LUAD.…”
Section: Discussionmentioning
confidence: 95%
“…For early stage lung cancer, due to the difficulty of tissue biopsy, there is still a lack of sensitive biomarkers to predict TMB and oncogenic driver mutations before surgery. With the development of liquid biopsy techniques, such as circulating tumor DNA (ctDNA) or circulating tumor cells (CTCs), it is possible to obtain the genomic mutation status from a blood sample; however both the sensitivity and cost are prohibitive Our study demonstrated that selected radiomics signatures using machine learning technique are feasible and effective to predict TMB and some driver mutations (EGFR and TP53) in patients with early stage LUAD.…”
Section: Discussionmentioning
confidence: 95%
“…Traditional approaches for molecular interrogation of CTCs include testing for genomic aberrations using immunostaining combined with fluorescence in situ hybridization (FISH) and real-time quantitative PCR (RT-qPCR) to evaluate the transcript levels of specific genes [17]. Yet, it is the development of single-cell technologies during the past decade that has enabled a comprehensive interrogation of CTCs from patients with various cancer types.…”
Section: Molecular Analysis Of Ctcsmentioning
confidence: 99%
“…Although they typically represent a minority of the CTCs found in the peripheral circulation, they have a metastatic potential that has been estimated to be 23 to 50 times greater than that of their single-cell counterparts [21]. In addition, the presence of CTC clusters and cluster size are associated with worse clinical outcome than the presence of single CTCs in multiple cancer types [17,21,[47][48][49][50]. Although the existence of CTC clusters has been known for decades [51][52][53][54][55], the biological mechanisms behind their formation, survival, dissemination, and superior metastatic ability are only partially understood [48].…”
Section: Single Ctcs Versus Ctc Clustersmentioning
confidence: 99%
“…Interestingly, even for early stage lung cancer, CTCs can be detected in 60-80% in patients (18,19). Recently, Murlidhar et al (20) reported that PV had significantly not only higher number of CTCs, but also larger CTC clusters compared to pre-operative and intra-operative peripheral vein among early stage lung cancer patients. Duan et al (17) demonstrated that CTC counts after lobectomy for lung cancer were significantly higher than those before PV interruption.…”
Section: Discussionmentioning
confidence: 99%